PROTEKSI ANARKISISME - Lukmanul Hakim (Universitas Islam Negeri Imam Bonjol Padang, 2013)
This paper illustrates the brawl that made the male students of SMK Padang, then look for a solution in the form of policy by competent parties overcome. This paper will explain the social and religious conditions of the students involved brawl, as well as the causes, forms, chronological brawl. The results of this study indicate that the fighting is done by the men's by way of a group of students. The reason to defend against another school,or attacking out of revenge. Leading to the anarchic attitude is a social life and a poor understanding of religion and problematic. Keywords : Gender-responsive education policies, expanding access, womenCopyright © 2013 by Kafa`ah All right reservedDOI : 10.15548/jk.v3i2.63